Client‐based Internet Protocol version 4‐Internet Protocol version 6 translation mechanism for Session Initiation Protocol multimedia services in next generation networks. Issue 3 (1st September 2013) - Chen, Whai‐En; Li, Ssu‐Hsien
Abstract : In the 'Next Generation Networks', 'Session Initiation Protocol' (SIP) is widely used to control multimedia (e.g. voice and video) sessions and 'Internet Protocol version 6' (IPv6) is adopted to provide enough addressing space. However, in the current stage of IPv6 deployment, the newly IPv6‐enabled device [i.e. typically internet protocol version 4 (IPv4)/IPv6 dual‐stack device] may connect to an existing IPv4 device. In the traditional 'server‐based solutions', the SIP server is modified to perform the IPv4–IPv6 translations to the SIP messages and the real‐time transport protocol (RTP) packets. However, the IPv4–IPv6 translations increase the call setup latency, the RTP transmission delay and the packet loss possibility. To reduce the drawbacks, this study proposes a 'client‐based solution', where the client (i.e. the end device) instead of the SIP server performs the IPv4–IPv6 translation. The authors utilise the message flows to elaborate three server based and the proposed client‐based solutions. In addition, the authors implement all solutions and deploy them in an IPv4–IPv6 interworking testbed. By using the testbed, the authors analyse these solutions in terms of the 'UA modification, the SIP Server modification, the call setup complexity and the RTP translation'.